The Role of Women in Advocacy and Community Reform - Asy'ari, Khoirul Hadi; Hayati, Dwi Astuti Wahyu Nur; Sa’diyah, Miftahus (Islamic Insights Journal, 2019)
In advocacy, women need to be identified so that we can attribute a role to their level. The judgment of the thing is part of his conception, which makes the knowledge of women's reality a priority. When we follow the evolution of women's life long ago to this day, we find that it is doomed.The role of women in advocacy: First and before I go on the subject must understand what is the area of advocacy that we want women to do it? Yes, it is the whole society, because this role can only be achieved if the society is included, whose life revives the nation and dies. When he says: "Believers and believers, some parents of some enjoin the good and end the evil and believe in God," he means what he says, because the knowledge of Virtue and Prevention of Vice can not be achieved only in the open society, which makes women contribute to the role of men. And the role of women in the reform of society, which is called the Holy Quran, which sees good and forbidding evil is no doubt and can not be denied only Makbar. The gift of the Holy Prophet in social life is conclusive evidence that Muslim women were present alongside men and at all levels. Here I am compelled to shorten some of the evidence that shows the constant and continuous presence in the life of the Prophet and after him in the open ages, which represented the finest era throughout Islamic history.Keywords: Women, Advocacy, Islam